EFEKTIVITAS PENDEKATAN PROBLEM SOLVING DALAM MENGEMBANGKAN KEMAMPUAN PEMECAHAN MASALAH MATEMETIKA SISWA SEKOLAH DASAR - Sabina Ndiung; Putri Yunita Suniarti Tecing; Eliterius Sennen (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2021)
Many factors cause the inability of students to solve math problems, including the role of educators in the learning process and learning activities that do not familiarize students with practicing creative thinking. Students are also rarely encouraged and involved to develop thinking skills and analyze and solve mathematical problems, teachers apply learning models and methods that are less varied and do not train students to solve problems. The purpose of this study is to describe the effectiveness of the problem solving approach in learning mathematics in elementary school and how to develop mathematical problem solving skills for students in elementary school. This type of research is a literature study using documentation techniques in collecting data. The steps to analyze the data of this research are to reduce the data then present the data and draw conclusions or verify the data. The results showed that the problem solving approach was considered effective for: (1) improving student learning outcomes, activities and responses; (2) improve students' understanding of mathematical concepts and communication skills; (3) improve students' mathematical problem solving abilities; and (4) improve students' critical thinking skills. Efforts that can be made by teachers to develop mathematical problem solving abilities of elementary school students are (1) applying a problem solving approach in learning and understanding and implementing problem solving steps properly and systematically; (2) train students to solve problems; (3) constructing non-routine items; and (4) implementing HOTS-oriented learning.